2014
DOI: 10.1177/1368430214556701
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric and complementary fit based on prototypical attributes of soccer teams

Abstract: Fitting in with a group extensively influences individual and group-related factors such as iden- AbstractResearch suggests that symmetry and complementarity are able to predict fit between an individual and a group. To date, fit has been described using knowledge, abilities, skills, values, personality, and the congruence between needs and their satisfaction. The aim of this study was to describe and analyze person-group fit based on the symmetric and complementary fit of prototypical attributes. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…Investigations of dyadic interactions between coaches and athletes (Jackson et al, 2011) showed increased commitment and a greater feeling of relatedness when both athlete and coach were high in agreeableness and conscientiousness, and decreased commitment and a weaker feeling of relation with higher dissimilarity in extraversion and openness to experience. In addition, Zepp and Kleinert (2015) found that the perceived supplementary fit of soccer players to their team (i.e., whether they perceived themselves to be similar to their team members) was associated with both higher subjective well-being and better individual performance.…”
Section: Person-environment Fitmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigations of dyadic interactions between coaches and athletes (Jackson et al, 2011) showed increased commitment and a greater feeling of relatedness when both athlete and coach were high in agreeableness and conscientiousness, and decreased commitment and a weaker feeling of relation with higher dissimilarity in extraversion and openness to experience. In addition, Zepp and Kleinert (2015) found that the perceived supplementary fit of soccer players to their team (i.e., whether they perceived themselves to be similar to their team members) was associated with both higher subjective well-being and better individual performance.…”
Section: Person-environment Fitmentioning
confidence: 99%
“…More precisely, we did not assess perceived person-environment fit (e.g., Zepp & Kleinert, 2015) but assessed fit in such a way that person-level and environment-level characteristics are measured separately, and then a fit index is derived (Rauthmann, 2021). Thus, in this study, we tested to what extent the level of congruence between two variables (here: individual and typical personality trait levels) is related to a specific outcome variable (here: different indicators of subjective well-being, e.g., sports-life satisfaction).…”
Section: Polynomial Regression and Subsequent Response Surface Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Teams that comprise members who think similarly and have similar personal characteristics often hold positive associations with success and well-being (e.g., Edwards, Cable, Williamson, Lambert, & Shipp, 2006;Kristof-Brown, Zimmerman, & Johnson, 2005;Zepp & Kleinert, 2014). This similarity or homogeneity refers to prototypical attributes especially and is, therefore, an influential factor when considering both intrateam processes and overall group performance (cf.…”
Section: Articlementioning
confidence: 99%